Special physical training and its effect on developing speed-strength and coordination, and on improving performance in the long jump for female students. - Saheb, Asst.L.Sabreen Mohammed (Sulaimani Journal for Humanities, 2026)
The current research aims to develop and implement specific physical training exercises for fourth-year female students at the College of Physical Education and Sports Sciences, University of Kufa, and to determine their effect on developing speed-strength and coordination, as well as improving the students' performance in the long jump. To achieve this objective, the researcher employed an experimental approach and a two-group design (equivalent to two groups): a control group and an experimental group. The research population consisted of 30 fourth-year female students at the College of Physical Education and Sports Sciences, University of Kufa, for the academic year 2024-2025. The research sample, which is part of the original population, was selected to study its characteristics. Twenty-four students were chosen and randomly divided into two groups of 12 each. The remaining six students were used for a pilot study. The researcher then developed and administered the tests for the pilot study. After confirming their validity, she administered pre-tests and ensured homogeneity and equivalence between the two groups. Following this, she implemented the training program, which comprised 24 training units conducted over eight weeks, with three units per week. After completing the training, the researcher administered post-tests to the research sample. Once the results were obtained, the statistical package SPAS was used to process the data and present the findings. Therefore, the researcher concluded... The researcher indicated that the prepared exercises play a role in developing strength characterized by speed, coordination, and effective long jump performance.
Keywords: Physical training; speed strength; coordination; and effective long jump performance